Preventive effects of minocycline in a neurodevelopmental two-hit model with relevance to schizophrenia - Giovanoli, S (Transl Psychiatry, 2016)
Maternal immune activation can increase the vulnerability of the offspring to develop neuroimmune and behavioral abnormalities in response to stress in puberty. In offspring of immune-challenged mothers, stress-induced inflammatory processes precede the adult onset of multiple behavioral dysfunctions. Here, we explored whether an early anti-inflammatory intervention during peripubertal stress exposure might prevent the subsequent emergence of adult behavioral pathology. We used an environmental two-hit model in mice, in which prenatal maternal administration of the viral mimetic poly(I:C) served as the first hit, and exposure to sub-chronic unpredictable stress during peripubertal maturation as the second hit. Using this model, we examined the effectiveness of the tetracycline antibiotic minocycline (MINO) given during stress exposure to block stress-induced inflammatory responses and to prevent subsequent behavioral abnormalities. We found that combined exposure to prenatal immune activation and peripubertal stress caused significant deficits in prepulse inhibition and increased sensitivity to the psychotomimetic drugs amphetamine and dizocilpine in adulthood. MINO treatment during stress exposure prevented the emergence of these behavioral dysfunctions. In addition, the pharmacological intervention blocked hippocampal and prefrontal microglia activation and interleukin-1β expression in offspring exposed to prenatal infection and peripubertal stress. Together, these findings demonstrate that presymptomatic MINO treatment can prevent the subsequent emergence of multiple behavioral abnormalities relevant to human neuropsychiatric disorders with onset in early adulthood, including schizophrenia. Our epidemiologically informed two-hit model may thus encourage attempts to explore the use of anti-inflammatory agents in the early course of brain disorders that are characterized by signs of central nervous system inflammation during development.